2013
DOI: 10.1108/13639511311329732
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming cop culture? Organizational justice and police officers’ attitudes toward the public

Abstract: Purpose -The purpose of this paper is to test theories of organizational justice in the context of a police agency. Design/methodology/approach -Structural Equation Modelling (SEM) was used to analyze data from a survey of officers in a police force in England. Findings -The SEM showed that organizational justice was associated with positive attitudes towards serving members of the public. This relationship was mediated by commitment to elements of community policing and, for community police officers, by gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(179 citation statements)
references
References 39 publications
3
170
0
6
Order By: Relevance
“…Myhill and Bradford (2013) reported a significant relationship between satisfaction with the agency and attitudes towards community policing and attitudes towards serving the public. This is an important link which suggests that job satisfaction experienced by police officers may help foster favourable attitudes towards police legitimacy and thereby citizen cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myhill and Bradford (2013) reported a significant relationship between satisfaction with the agency and attitudes towards community policing and attitudes towards serving the public. This is an important link which suggests that job satisfaction experienced by police officers may help foster favourable attitudes towards police legitimacy and thereby citizen cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of US officers, Farmer et al (2003) observed that both distributive and procedural fairness had positive associations with job satisfaction. Among British officers, a composite measure of perceptions of organisational fairness had a positive relationship with satisfaction from working at the agency (Myhill and Bradford, 2013). In a study of South Korean officers, distributive justice had a significant positive relationship with job satisfaction (Crow et al, 2012).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dans le contexte policier, quelques rares études soulignent globalement les effets positifs de la justice sur différentes variables comme la satisfaction, l'implication organisationnelle et la performance (Myhill et Bradford, 2013;Tyler et al, 2007;Farmer, Beehr et Love, 2003).…”
Section: La Justice Organisationnelleunclassified
“…Working in accordance with the dominant office culture was also highlighted as an external force that influenced how practitioners treated parents during IPA practice. This finding reflects the extant procedural justice literature, which highlights the role of organisational culture in encouraging people to enact procedural justice (Colquitt et al, 2001;Myhill & Bradford, 2013). It was also discussed in chapter seven that professional frameworks and strengthbased orientations to practice could also support the enactment of procedural justice during IPA.…”
Section: Practitioners As Providers Of Procedural Justice To Parentsmentioning
confidence: 49%